Work Experience for the Rural, Special Needs Student A Pipe Dream or a Possibility? - Elrod, G. Franklin ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
Work experience programs help rural handicapped, learning disabled, and economic/culturally disadvantaged students to make the transition from school to young adulthood. Reading, mathematics, and social difficulties evident in school impact work behaviors in later life. Other factors impacting work behaviors include cultural differences, economic hard times, limited vocational alternatives, and lack of response by educators. Vocational and pre-vocational work experience programs can assist in changing established behaviors and developing work behavior appropriate to rural employment needs. Procedures for building work experience programs in rural schools include locating on-campus and off-campus job sites, approaching employers, assessing requirements of transporting students to sites, training on-site supervisors, teaching work-related skills, obtaining liability waivers, and developing a continuum of work experience placement such as piece-work in the classroom, followed by on-campus job, then off-campus placement. Suggestions for program success include: extend work experience to junior high/middle schools; look at student capabilities, not disabilities; involve parents; use contracts to formalize the program for students, employers, and school personnel; conduct program evaluations. Appendices provide sample forms for evaluating potential work experience sites, student personal information/self-evaluation, work evaluation forms, liability waivers, job training agreement, work experience contract, and evaluation questionnaires. (LFL)
ERIC Note: Paper presented at the Annual Conference of the National Rural and Small Schools Consortium (Bellingham, WA, October 7-10, 1986).
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavior Change; Disabilities; Disadvantaged; Educational Needs; Elementary Secondary Education; Job Skills; Normalization (Handicapped); Questionnaires; Rural Education; Rural Youth; School Business Relationship; Special Education; Special Programs; Student Experience; Vocational Education; Work Attitudes; Work Experience Programs; Reports, Descriptive; Speeches/Meeting Papers